Wearable electronic devices with shape memory and stretchability for comfort fitting - Naveen, Balasundaram Selvan (Nanyang Technological University, 2022)
Programmability will significantly increase the scope of wearable electronics in terms of their usage in various industries. It also provides comfort fitting to the customers as the shape of the device can be easily fixed depending on the needs of the customer. Comfort fitting also requires the device to be functional at normal body temperature of a human being (37°C). Significant research has been taking place in improving the stretchability of wearable electric devices. However, these devices immediately return to their original shape once the force (used to stretch the devices) is released. This leads to the development of discomfort in the users in whichever part of the body it is applied to. Hence, this report aims to address this critical issue by developing a new material that has the ability to hold its shape (programmable) when stretched and provide the necessary comfort to its users. This material has the ability to be programmed at body temperature which adds to the comfortability factor. This report studies the elastic and shape memory properties of this material and its potential usage in developing new wearable electric devices that are not only stretchable but also programmable for comfort fitting. A cost effective and easy fabrication process is also discussed to embed seemingly non-stretchable electronic substrates into these shape memory materials to fabricate stretchable electronic samples and their stretchability are also studied. Finally, this report discusses the future prospects for the advancement of wearable technology using such programmable materials.